Histories of fascism and anti-fascism in Australia
1 online resource.
Keywords: "Histories of Fascism and Anti-Fascism in Australia provides a history of fascist movements and anti-fascist resistance in Australia over the last century. In recent years, the far right has become a resurgent force across the globe, resulting in populist parties securing electoral victories, social movements organising on the streets, and acts of right-wing terrorism. Australia has not been immune to this. However, this is not merely a recent phenomenon; it has a long history of fascist and far-right groups and individuals. These groups have attempted to situate themselves within the wider settler colonial political landscape, often portraying themselves as the inheritors of a violent and exclusionary colonial past. Concurrently, these groups have linked into globalised anti-communist and white supremacist networks. At the same time, Australia has often seen resistance to fascism and the far right, from the political centre to the far left. Covering the period from the 1920s to the present day, and featuring insights from historians, sociologists, and political scientists, this book provides the most detailed account of this fascinating and important topic. This book will be of interest to students and activists with an interest in the extreme right and anti-fascism as well as Australian history, politics, and society"--